New generation Amberlite XAD resin for the removal of metal ions: A review - Ahmad, Akil (Chinese Academy of Sciences, 2015)
The direct determination of toxic metal ions, in environmental samples, is difficult because of the latter's presence in trace concentration in association with complex matrices, thereby leading to insufficient sensitivity and selectivity of the methods used. The simultaneous removal of the matrix and preconcentration of the metal ions, through solid phase extraction, serves as the promising solution. The mechanism involved in solid phase extraction (SPE) depends on the nature of the sorbent and analyte. Thus, SPE is carried out by means of adsorption, ion exchange, chelation, ion pair formation, and so forth. As polymeric supports, the commercially available Amberlite resins have been found very promising for designing chelating matrices due to its good physical and chemical properties such as porosity, high surface area, durability and purity. This review presents an overview of the various works done on the modification of Amberlite XAD resins with the objective of making it an efficient sorbent. The methods of modifications which are generally based on simple impregnation, sorption as chelates and chemical bonding have been discussed. The reported results, including the preconcentration limit, the detection limit, sorption capacity, preconcentration factors etc., have been reproduced.